2013
DOI: 10.21660/2013.9.62312
|View full text |Cite
|
Sign up to set email alerts
|

Collapsibility in Calcareous Clayey Loess: A Factor of Stress-Hydraulic History

Abstract: ABSTRACT:The re-use of excavated loess in embankments needs a good understanding of its long-term mechanical response. Among the many collapse controlling factors, stress and hydraulic history are of significant importance as certain combination of these can alter the packing state to great extents. However, published works on stress path-packing state interaction is limited to clayey silts, underreporting the contribution of carbonates. Works on hydraulic path-packing state interaction lacks physical evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For granular materials that are large (i.e., a mix of solids with various minerals of various crystalline qualities), their hydromechanical properties, such as air-entry value, the threshold of collapsibility, and static flow potential, are associated with structure. In an earlier work [32], we showed that the hydraulic hysteresis that typically appears in soil-water characteristics curves is probably controlled by pore spaces of a certain size in soils. In that study [32], a series of suction-controlled oedometer experiments were conducted on a synthetic geo-material and the findings were paired with real-time measurements of the changing structure.…”
Section: Universal Fractals For Granular Materials At Largementioning
confidence: 84%
See 1 more Smart Citation
“…For granular materials that are large (i.e., a mix of solids with various minerals of various crystalline qualities), their hydromechanical properties, such as air-entry value, the threshold of collapsibility, and static flow potential, are associated with structure. In an earlier work [32], we showed that the hydraulic hysteresis that typically appears in soil-water characteristics curves is probably controlled by pore spaces of a certain size in soils. In that study [32], a series of suction-controlled oedometer experiments were conducted on a synthetic geo-material and the findings were paired with real-time measurements of the changing structure.…”
Section: Universal Fractals For Granular Materials At Largementioning
confidence: 84%
“…In an earlier work [32], we showed that the hydraulic hysteresis that typically appears in soil-water characteristics curves is probably controlled by pore spaces of a certain size in soils. In that study [32], a series of suction-controlled oedometer experiments were conducted on a synthetic geo-material and the findings were paired with real-time measurements of the changing structure. The geomaterial constituted an open assemblage of crystalline solids (quartz, sesquioxides, and phyllosilicates) as well as amorphous matter.…”
Section: Universal Fractals For Granular Materials At Largementioning
confidence: 84%
“…An important example of DEM advantage in understanding the behaviour of open-structured particulate matters is the impacting of fines fraction on seepage-induced boiling and flow (static liquefaction) potential of porous granular soils. Hydromechanical soil properties, such as air-entry value, collapsibility, and potential of flow, are associated with the overall layout of interconnected micro (< 0.001 µm), meso (0.001-0.25 µm and 0.3-1.5 µm) and macro (2-20 µm) voids, and the degree to which these contain fines at any one time [31,32]. These 'fractions' of void spaces control soil packing states [33].…”
Section: Microscale: Discrete Element Methods (Dem)mentioning
confidence: 99%
“…Subsequently, the nanotechnological field represents a novel methodology in all sciences. This methodology could be utilized in geotechnics designing within two different ways: (1) considering the structures for soils within nm scales for improving the way we comprehend soils, just as examining the exhibition for soil treating by various nanostructures, also (2) leading soils misuse by the nuclear or atomic scale. Such can be encouraged by the expansion of nanomaterials as an outside prop gasp for soils (Majeed and Taha, 2013).…”
Section: Introductionmentioning
confidence: 99%